The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1164/rccm.2204037
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Challenge Tests in Patients with Asthma Sensitized to Cats

Abstract: Our aim was to compare bronchial responses to major cat allergen (Fel d 1) in individuals with intermittent asthma sensitized to cats (19 subjects) according to the droplet particle size. We used three nebulizers, which delivered particles with mass median aerodynamic diameters of 1.4, 4.8, and 10.3 microm. A dosimeter nebulizer was used. The cat allergen was diluted to obtain the same amount of Fel d 1 per puff with each nebulizer. Each patient underwent three methacholine bronchial challenge tests (BCT), eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Subjects sensitized to small particles were more likely to have higher airway responsiveness compared with subjects sensitized only to large particles. That contradicts results of previous studies where larger aerosols of adenosine monophosphate ( 41 ), methacholine ( 14 ), cat allergen ( 42 ), and mite allergen ( 43 ) gave more immediate responses than smaller particles. The same quantity could be delivered in both large and small airways with the nebulizer, but the concentration relative to the area of deposition in the larger airways would be higher as deposition of the same dose in the small airways could be insufficient to achieve similar airway bronchoconstriction due to the larger area of the small airways.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Subjects sensitized to small particles were more likely to have higher airway responsiveness compared with subjects sensitized only to large particles. That contradicts results of previous studies where larger aerosols of adenosine monophosphate ( 41 ), methacholine ( 14 ), cat allergen ( 42 ), and mite allergen ( 43 ) gave more immediate responses than smaller particles. The same quantity could be delivered in both large and small airways with the nebulizer, but the concentration relative to the area of deposition in the larger airways would be higher as deposition of the same dose in the small airways could be insufficient to achieve similar airway bronchoconstriction due to the larger area of the small airways.…”
Section: Discussioncontrasting
confidence: 90%
“…To our knowledge, few studies ( 14 , 41 43 ) examined the effects of IgE sensitization with regard to particle size on the airways responsiveness, lung function, and markers of systemic inflammation during bronchial challenge tests. Differential immediate and late allergic responses were reported in relation to particle size with small allergen particles leading to significantly lower FEF 25–75 at 24 h after provocation compared with large particles ( 42 ). Our study demonstrated a differential response to smaller allergen particles (for example cat and dog) leading to an increase of F E NO 50 , mainly explained by an increase in airway concentration of NO but no effect on alveolar contribution to NO.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate bronchial response to Fel d 1 appears to be located in the proximal airways. The concentration of Fel d 1 required to induce a positive bronchial response in subjects with intermittent asthma was 20 times less when the allergen was carried by large particles (10.3 μm) than when Fel d 1 was carried by small particles (1.4 μm) [ 36 ]. However, a more recent article suggests that exposure under natural conditions to cat allergens (and not just to Fel d 1) induces a more peripheral airway obstruction [ 37 ].…”
Section: Main Textmentioning
confidence: 99%
“…Indeed, whereas in the Boehlecke study the mass median aerodynamic diameter of endotoxin particles was 4.9 μm, we chose to nebulize particles with a medium mass aerodynamic diameter of 10 μm. Indeed, we have recently demonstrated that the levels of Fel d 1 that induced immediate bronchial response in asthmatic patients were 20 times lower when the allergen was carried by large particles [18]. According to preliminary data on airborne endotoxin measurements with cascade impactor in swineries, we also nebulized endotoxin on large particles.…”
Section: Discussionmentioning
confidence: 99%